Aphakic correction using retropupillary iris claw lens following a therapeutic keratoplasty (Indian Journal of Case Reports, 2020)
Retropupillary iris claw lens implantation is a safe, simple, and effective alternative to anterior chamber or scleral-fixated intraocular lens implantation in post keratoplasty cases. We, hereby, report a case of retropupillary iris claw lens implantation for aphakia following a therapeutic keratoplasty. A 55-year-old male who had a large fungal keratitis underwent therapeutic keratoplasty, and subsequently, a retropupillary iris claw lens implantation. A 6-month follow-up showed a clear graft with stable iris claw lens and no comorbidities.